(untitled) (MAUSAM, 1951)
This paper is in continuation of an earlier one by the author which appeared in this journal. It deals with the study of carbon dioxide content of the soil air of a sugarcane field. It is shown that the carbon dioxide content of the soil air is subject to local variations. An attempt has been made to see whether this local variation of soil air carbon dioxide is in any associated with the vigyour of the sugarcane plants. It is found, as a result that greater concentration of soil an carbon dioxide is Associated with taller plants and larger foliage development. The paper also describes A pot-culture experiment performed to compare the development of cotton plants irrigated with carbonated water. Plants grown under irrigation with carbonated water are found to be taller and having greater foliage development.